The Impact of Parsing and Meaning in the Interpretative Orientations of Tusee (in his Al.Tibian in the explanation of the Qur 'an) - Asst.Prof. Gazi Mutashar Hamza al-Badri (Journal of College of Education, 2023)
Parsing has an effect on meaning as it eliminates ambiguity. It also has the advantage of flexibility in preposing and postposing the word order without affecting the semantic function. This feature is distinct in the Arabic language because it is marked with diacritics, but the other languages lack this feature, and a word can only hold one position, and accordingly have less flexibility in this respect. Thus, parsing eliminates ambiguity in the meaning of utterances, and manifests the intentions of speakers. No doubt, for Tusee, parsing and meaning are two main principles in his hermeneutic orientation of interpreting the Qur'an, explicating the implicatures that diversity in parsing can indicate. The research reinforces the idea that the meaning had a clear impact on the multiplicity of parsing. It is the basis in parsing and constrains the orientation in parsing, for the Arabic language being so extended in vocabulary and fertility of diction. Qur'anic readings can render diversity in parsing with diversity in meaning, and thus affecting the religious injunction. The study sheds light on the impact of parsing and meaning due to diversity of Tusee's hermeneutic orientation of the interpretation in ( The Bayan in Interpreting the Qur'an). I hope that this with be of great benefit.
Keywords: Parsing , meaning , interpretive orientations